Knowledge, Attitudes, and Practices Regarding Smoking Prevention Among Students of Jakarta Global University - Adina, Anugerah Budipratama; Zhafira, Bilqis; Indriani, Melis; Nopratilova, Nopratilova; Nugroho, Dedy (Pustaka Media Publishing, 2025)
ABSTRACT Students need to have good knowledge, attitudes, and behaviors regarding healthy living, particularly in avoiding smoking and understanding its dangers, to serve as positive role models for the broader community and younger generations. This study aims to assess the knowledge, attitudes, and practices (KAP) of students related to smoking habits at Jakarta Global University (JGU). The research method employed is a quantitative descriptive approach using an online survey with a questionnaire. The sample consisted of 105 respondents. The results indicate that, among the 105 respondents, the majority of students are aged 18 to 22 years (86.7%), with the largest proportion coming from the pharmacy department (43.8%). Students' knowledge about the dangers of smoking is fairly good, though there are challenges in enhancing precise understanding of the serious health risks associated with smoking. Attitudes show high confidence in the effectiveness of anti-smoking campaigns, with 67.6% of respondents believing that smoking has a very detrimental impact on health. Furthermore, preventive practices against smoking are also relatively high, with 64.8% of students supporting smoking cessation programs and replacing smoking habits with healthy activities. The conclusion of this study is that the knowledge, attitudes, and behaviors related to smoking among students are categorized as good. The findings underscore the importance of further education on effective smoking prevention, especially in the context of reducing health risks associated with smoking.